Generation of a Genetically Modified Chimeric Plasmodium falciparum Parasite Expressing Plasmodium vivax Circumsporozoite Protein for Malaria Vaccine Development - Miyazaki, Yukiko; Marin-Mogollon, Catherin; Imai, Takashi; Mendes, António M.; van der Laak, Rianne; Sturm, Angelika; Geurten, Fiona J. A.; Miyazaki, Shinya; Chevalley-Maurel, Severine; Ramesar, Jai; Kolli, Surendra K.; Kroeze, Hans; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Chimeric rodent malaria parasites with the endogenous circumsporozoite protein (csp) gene replaced with csp from the human parasites Plasmodium falciparum (Pf) and P. vivax (Pv) are used in preclinical evaluation of CSP vaccines. Chimeric rodent parasites expressing PfCSP have also been assessed as whole sporozoite (WSP) vaccines. Comparable chimeric P. falciparum parasites expressing CSP of P. vivax could be used both for clinical evaluation of vaccines targeting PvCSP in controlled human P. falciparum infections and in WSP vaccines targeting P. vivax and P. falciparum. We generated chimeric P. falciparum parasites expressing both PfCSP and PvCSP. These Pf-PvCSP parasites produced sporozoite comparable to wild type P. falciparum parasites and expressed PfCSP and PvCSP on the sporozoite surface. Pf-PvCSP sporozoites infected human hepatocytes and induced antibodies to the repeats of both PfCSP and PvCSP after immunization of mice. These results support the use of Pf-PvCSP sporozoites in studies optimizing vaccines targeting PvCSP.